ADDRESSING HEALTH LAW CHALLENGES IN ELECTIONS: POLICY INNOVATIONS TO IMPROVE ACCESSIBILITY FOR VULNERABLE VOTERS - Hartono Tasir Irwanto; Imran Eka Saputra; Ali Rahman (Fakultas Hukum, Universitas Sawerigading Makassar, 2026)
Elections as the foundation of democracy should ensure inclusive participation for all citizens, including vulnerable groups such as the elderly, people with disabilities, and individuals with chronic health conditions. However, the implementation of electoral regulations in Indonesia often fails to address the health needs of these groups. The gap between the ideal national policy and the reality of implementation on the ground remains a serious challenge that has yet to be resolved. This study evaluates the effectiveness of health regulations in supporting vulnerable voters' access during elections. Using a literature review-based qualitative approach, data was collected from academic literature, national policies, as well as previous research reports. Findings show that although some health protocols have been implemented, barriers such as limited medical facilities at polling stations, lack of budget, and low levels of socialization still prevent vulnerable groups from fully participating. One important innovation proposed is the integration of information technology to facilitate access to health information, especially for voters with special needs. This technology can help voters plan their attendance at polling stations in a more health-friendly manner. On the other hand, more concrete solutions include strengthening regulations with clear technical guidelines, specialized training for polling station officers to understand the needs of vulnerable groups, and synergy between central and local governments to ensure adequate resource allocation.